Answer:
2 solutions: x= -1 x=
![(1)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/f0qcv9cek84ihznc3s7uf39dlk9xfru67q.png)
Explanation:
You could solve this 2 ways, either by factoring or using the quadratic formula.
Factoring:
Use the formula:
![a^2-b^2=(a-b)(a+b)](https://img.qammunity.org/2022/formulas/mathematics/high-school/l0mehc2b11f8qfsnoadjcyyift62d57m9g.png)
(4x+1-3)(3x+1+3)=0
(4x-2)(4x+4)=0
No we can factor out a 2 and a 4:
2(2x-1)4(x+1)=0
Divide both sides by 2x4:
(2x-1)(x+1)=0
Now set both equal to 0:
2x-1=0
x+1=0
x=
![(1)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/f0qcv9cek84ihznc3s7uf39dlk9xfru67q.png)
x=-1
For quadratic formula:
Use the formula:
![(a+b)^2=a^2+2ab+b^2](https://img.qammunity.org/2022/formulas/mathematics/high-school/7y2nbal3fjhbii5mxnvz1yv245ucy6afwj.png)
First expand the expression:
![16x^2+8x-8=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/wpp07yacaoii43kyncv46ucxlwac0rb5ec.png)
Divide both sides by 2:
![2x^2+x-1=0](https://img.qammunity.org/2022/formulas/mathematics/high-school/wms9rwrpt08s9ijumviuq6jmrqtml5g3ay.png)
Now we can plug it in:
a=2
b=1
c=-1
![x=\frac{-1+\sqrt{1^(2) -4(2)(-1)} }{4}](https://img.qammunity.org/2022/formulas/mathematics/high-school/5drho8ccvzsnhz18tx9wvlwzvgtjw36hy2.png)
![x=(-1+√(9) )/(4)](https://img.qammunity.org/2022/formulas/mathematics/high-school/tvn88730l7quu961xbdg47cwk6vtep3y1x.png)
![x=(-1+3)/(4)](https://img.qammunity.org/2022/formulas/mathematics/high-school/2fo38tybtvo9h58cily5o6b5r7lb7wmd2i.png)
Now solve for each solution:
![x=(-1+3)/(4) \\\\x=(-1-3)/(4) \\\\x=(1)/(2)\\x=-1](https://img.qammunity.org/2022/formulas/mathematics/high-school/6vaezqhrksvbw1ld9cx2f69ax76sgwjv99.png)
Either way you get the same answer, hope this helps! :)